THE EFFECTS OF INDEPENDENT COMMISSIONER, MANAGERIAL OWNERSHIP, FOREIGN OWNERSHIP, AND PROFITABILITY ON INTELLECTUAL CAPITAL - Yonata, Patricia Nikita; Susanto, Liana (International Journal of Application on Economics and Business, 2023)
This research is designed to determine the factors that affect intellectual capital in Indonesia's manufacturing companies listed on its stock exchange. The research periods are from 2018-2020. In this research, 31 manufacturing companies were taken as samples by the purposive sampling method. The research data were analysed using multiple linear regression analysis techniques. Profitability has a significant positive effect on intellectual capital, as shown by the results of this research. Intellectual capital is not significantly affected by independent commissioner, managerial ownership and foreign ownership.